2013
DOI: 10.1039/c3ce00042g
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low temperature structure determination of a Mn12 single-molecule magnet and the interplay between lattice solvent and structural disorder

Abstract: Ultra-low temperature structure determination of a Mn 12 single-molecule magnet and the interplay between lattice solvent and structural disorder3{

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…A similar behaviour has been later reported also in lanthanide based complexes. 55,56,68,69 In the present case, the heterodinuclear structural unit of 2 form a 3D network with water molecules from crystallization: 49 it can then be suggested that when the sample was pressed in a pellet this resulted in a partial loss of solvent. This is of peculiar importance, since the water molecules in the lattice generate an extended network of hydrogen bonds, which might be able to transmit weak exchange coupling interactions.…”
Section: Discussion On Ageingmentioning
confidence: 68%
“…A similar behaviour has been later reported also in lanthanide based complexes. 55,56,68,69 In the present case, the heterodinuclear structural unit of 2 form a 3D network with water molecules from crystallization: 49 it can then be suggested that when the sample was pressed in a pellet this resulted in a partial loss of solvent. This is of peculiar importance, since the water molecules in the lattice generate an extended network of hydrogen bonds, which might be able to transmit weak exchange coupling interactions.…”
Section: Discussion On Ageingmentioning
confidence: 68%
“…104 Accordingly, we set S Z ¼ 10 as a constraint on the GAUSSIAN 09 and VASP electron and spin distributions we computed. In VASP, we optimized the atomic positions and used the experimental lattice parameters of Farrell et al 105 (Cambridge Structural Database ID BESXAA). In GAUSSIAN 09, we used an isolated molecule and optimized the atomic positions.…”
Section: Collinear and Non-collinear Magnetic Materialsmentioning
confidence: 99%
“…However, in order to understand the magnetic anisotropy in Co­(II) mononuclear complexes, which tends to dictate the resulting magnetic properties, a thorough understanding of the geometrical environment of the Co­(II) is required . In particular, where low temperature magnetic measurements are used to confirm certain properties, it is also important to be certain of the structure in the temperature range at which the measurement is carried out (typically < 10 K) …”
Section: Introductionmentioning
confidence: 99%
“…28 In particular, where low temperature magnetic measurements are used to confirm certain properties, it is also important to be certain of the structure in the temperature range at which the measurement is carried out (typically < 10 K). 29 We present herein a systematic variable temperature single crystal X-ray diffraction study of [Co II (NO 3 ) 3 (H 2 O)-(HDABCO)] (1), 30 evidencing a disorder-to-order, singlecrystal to single-crystal phase transition accompanied by a clear coordination switch from a 5-to a 7-coordinate complex below 140 K. The magnetic studies of 1 confirm slow relaxation of the magnetization under an applied dc field, originating from a large easy-plane magnetic anisotropy. We stress the merits of thorough low temperature crystallographic investigations of single-ion magnets, especially where the ligands involved can display a variety of coordination modes.…”
Section: ■ Introductionmentioning
confidence: 99%